2018
DOI: 10.1002/ca.23248
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional relationships between external abdominal oblique muscle and posterior layer of thoracolumbar fascia

Abstract: The abdominal muscles are important for the stability of the lumbar region through the thoracolumbar fascia (TLF). However, there is not full agreement regarding the posterior transversal continuity of the external abdominal oblique muscle (EO) with the TLF. To clarify this point, 10 cadavers and computed tomography (CT) images from 27 subjects were used to evaluate the transversal continuity of the TLF with the abdominal muscles. The width of the fascial continuity of the EO with the posterior layer of TLF al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Contrary to public opinion, according to which CS preserves women from post-partum complications, our study shows that CS, especially scar formation, may be one of the most important co-factors in developing muscle deficit and asymmetries and altering sliding within the fascial plane, which could, in turn, be the direct or indirect cause of SP, ABP, LBP, and PVP. Our study confirms the concept of a ’theory of a whole-body fascial linkage’ from the clinical point of view [ 20 ], which may help us to better understand the clinical symptoms of musculoskeletal pain, such as LBP resulting from the abdominal (e.g, CS, abdominal surgery) or pelvic region due to fascial continuity, and to develop appropriate treatments. Conversely, pelvic or abdominal symptoms may be present in low back disorders.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Contrary to public opinion, according to which CS preserves women from post-partum complications, our study shows that CS, especially scar formation, may be one of the most important co-factors in developing muscle deficit and asymmetries and altering sliding within the fascial plane, which could, in turn, be the direct or indirect cause of SP, ABP, LBP, and PVP. Our study confirms the concept of a ’theory of a whole-body fascial linkage’ from the clinical point of view [ 20 ], which may help us to better understand the clinical symptoms of musculoskeletal pain, such as LBP resulting from the abdominal (e.g, CS, abdominal surgery) or pelvic region due to fascial continuity, and to develop appropriate treatments. Conversely, pelvic or abdominal symptoms may be present in low back disorders.…”
Section: Discussionsupporting
confidence: 82%
“…Although the fascia has been hypothesized to play a role in the pathogenesis of chronic pain, no investigation quantitatively evaluating the fasciae in CS or VA subjects can be found in the literature. From the fascial point of view, abdominal muscles are in continuity with the thoracolumbar fascia and the pelvic floor [ 20 , 21 , 22 , 23 ]. It has been demonstrated that they work with great synergy [ 24 ], guaranteed by fascial continuity.…”
Section: Discussionmentioning
confidence: 99%
“…Within oblique musculature, the EO would be less affected by the AHM than the IO because is a more global torque-producing muscle, less involved in segmental spinal stability [ 68 ]. However, interestingly, the medial fibers of the EO are anatomically related to the thoracolumbar fascia and thus biomechanically would have some stabilizing role as well [ 27 , 72 ]. As a result, both obliques and the TrA inevitably would work together to flatten the abdomen during the AHM [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The superficial and deep cervical fascias surround the viscera and the suprahyoid and infrahyoid muscles, to flow anterolaterally to the superficial muscles of the neck (SCM, subclavian muscle, platysma), to the clavicle, the sternal body; at the thoracic outlet level the fasciae divide to cover the anterior (fascia thoracis superficialis) and deep chest area (as described in the previous first part [23]. The thoracis superficialis fascia covers the pectoralis major muscle, the pectoralis minor, the serratus, the sternalis (when present), and is connected to the lateroposterior musculature since the superficial fascia is the same [24][25]. The deep fascia of the neck before entering the mediastinum, at the cervical level, covers the thyroid posteriorly, while anteriorly and laterally the superficial fascia covers the thyroid, the thyroid muscles, the Berry ligament (between the thyroid and the laryngeal-tracheal complex); the superficial fascia builds the lingual frenulum (between the arch of the jaw and the buccal floor), involving the sublingual glands and submandibular ducts [26][27].…”
Section: Figure 1: the Images Show The Close Relationship Between Thementioning
confidence: 99%
“…The pectoralis major continues with the abdominal fascia, including the aponeurosis of the external oblique; the abdominal fascia covering the rectus abdominals involves the rib cartilages (V-VII) and the pubic symphysis. The abdominal fascia and the underlying abdominal muscles (rectus abdominis, obliques and transversus abdominis), together with the transversalis fascia, communicate with fascial continuity with the thoracolumbar fascia ( Figure 5) [25]. The transversalis fascia (TF) is the continuation of the endothoracic fascia and stands between the epimysium of the diaphragm muscle and the underlying viscera.…”
Section: Figure 1: the Images Show The Close Relationship Between Thementioning
confidence: 99%